The lost duke of Wyndham - Quinn, Julia, 1970- (London : Piatkus, 2021)
Highwayman Jack Audley has never wanted to be responsible for an ancient heritage and the livelihood of others. But when he is recognized as the long-lost son of the House of Wyndham, his carefree life is over. If his birth proves to be legitimate, Jack will find himself with the one title he has never wanted: Duke of Wyndham. Grace Eversleigh has spent the last five years toiling as the companion to the dowager Duchess of Wyndham. It is a thankless job, with very little break from the routine... until Jack Audley lands in her life.
Julia Quinn started writing her first book one month after finishing university and has been tapping away at her keyboard ever since. The No. 1 New York Times bestselling author of more than two dozen novels, she is a graduate of Harvard and Radcliffe Colleges and is one of only sixteen authors ever to be inducted in the Romance Writers of America Hall of Fame. She lives in the Pacific Northwest with her family.
Keywords: Brigands and robbers -- Fiction; Inheritance and succession -- Fiction; Love stories; Historical fiction